Специальные профилактические меры борьбы с умышленными убийствами, нанесениями тяжких телесных повреждений и изнасилований, совершенных с особой жестокостью в Кыргызской Республике (Journal of actual problems of jurisprudence, 2019)
The article covers preventive measures of struggle against intended killings, infl iction of serious bodily injuries or harm, forciblerapes with extreme atrocity. Based on the results, it is offered concrete ways of solution of the revealed and de fi ned problems for preventive measures development, the most effi ciently prevented development as well as reduction of quantity of the speci fied crimes inKyrgyzstan.